Antiviral activity of silver nanoparticles against the influenza A virus - Krystyna Naumenko; Svitlana Zahorodnia; Calin V. Pop; Nodari Rizun (Elsevier, 2023)
Viral infections occupy an essential place in modern medicine, particularly a large group of diseases caused by the influenza viruses. They are rapidly transmitted and mutate quickly, which can lead to significant socio-economic consequences. Silver nanoparticles (AgNPs) are considered to be an effective antimicrobial agent. This study shows that they have strong antiviral properties against the influenza A virus infection. Their absence of cytotoxicity at inhibitory concentrations demonstrates that they could be an effective antiviral agent against this virus. As AgNPs inhibit the influenza A virus replication and spread, they could also be successfully used as a post-infection virostatic agent.